The palaeobiogeographical spread of the acritarch Veryhachium in the Early and Middle Ordovician and its impact on biostratigraphical applications - Servais, Thomas (2014)
The genus Veryhachium Deunff, 1954, is one of the most frequently documented acritarch genera, being recorded from the Early Ordovician to the Neogene. Detailed investigations show that Veryhachium species first appeared near the South Pole in the earliest part of the Tremadocian (Early Ordovician). The genus was present at high palaeolatitudes (generally>60° S) on the Gondwanan margin during the Tremadocian before spreading to lower palaeolatitudes on the Gondwanan margin and other palaeocontinents (Avalonia and Baltica) during the Floian. It became cosmopolitan in the Middle and Late Ordovician. Although useful for distinguishing Ordovician from Cambrian strata, the diachronous first appearance data of Veryhachium morphotypes mean that they should be used with caution for long-distance correlation.